The Rapidly Evolving Treatment Landscape in Newly Diagnosed Multiple Myeloma: Current Status and Future Directions - Yuxin Liu; Clifton Mo; Monique Hartley-Brown; Shonali Midha; Adam S. Sperling; Giada Bianchi; Omar Nadeem; Betsy O’Donnell; Jacob Laubach; Paul G. Richardson (healthbook TIMES. Oncology Hematology)
Over the past two decades, significant progress has been made in the management of multiple myeloma (MM), leading to the development of novel therapeutic approaches and treatment regimens to improve patient outcomes. In patients with newly diagnosed MM (NDMM), the introduction of anti-CD38 monoclonal antibodies daratumumab and isatuximab has significantly extended patient survival while maintaining a manageable toxicity profile and building upon the success of highly active triplet combinations incorporating immunomodulatory drugs, proteasome inhibitors and dexamethasone. Treatment strategies based on the assessment of minimal residual disease (MRD) negativity, a strong prognostic marker for durable responses, allow for improved decision making in MM management. Active ongoing research aims to assess how novel therapies may improve outcomes in both frontline and maintenance settings. This review article discusses recent advances in NDMM therapy, with a focus on quadruplet versus triplet anti-CD38 mAb-based regimens and MRD-driven approaches, as well as emerging alternative therapeutic strategies, including transplant-sparing approaches to meaningfully improve patient outcome. Ongoing trials are also outlined, including the data presented at the 65th American Society of Hematology (ASH) Annual Meeting & Exposition, the 2024 American Society of Clinical Oncology (ASCO) Annual Meeting, the 2024 European Hematology Association (EHA) Congress and the 21st International Myeloma Society (IMS) Annual Meeting 2024.